Transformation in the Nature of American Economics and Establishing Neoclassical Economic Technology - Atanasova, Veselina (Research Papers, 2014)
The study briefly focuses on the processes of gradual, though not linear, establishment of the dominance of Neoclassical view after interwar period, following the history of American economics. It is shown that by that (interwar) period there have already been present historically developed components, needed for the turn in the character of the economic theory and its application. This change is associated with converting effects of external determinants in the development of economics – and general aspects, or instruments, of the method of economics as a whole, into intrinsic features and specific tools of the advancing Neoclassical economics. Basically exploited is Mary Morgan’s (2001) conception of the natural interdependences in the processes of functioning of both sides of economics – the theoretical and the applied one – in the form of Economic technology. In this direction It is suggested, development of American, - and world, - economics from around 1930s-1940s through 2000s to be interpreted through the prism of the formation and functioning (applying) of grand neoclassical economic technology, component (dominated) part of which appears to be the Keynesian economic technology.